Negotiating Identity and Confronting Racism: A Postcolonial Analysis of Mohsin Hamid’s The Face in the Mirror - Soomro, Javairia; Ajmal, Muhammad; Khan, Saima Yousaf (Pakistan Languages and Humanities Review, 2025)
The main objective of this research is to analyze Mohsin Hamid’s The Face in the Mirror which highlights issues of identity and racism. This research is qualitative in nature and utilize a postcolonial theoretical framework of Homi K. Bhabha. The analysis is undertaken within the post-colonial context to show the struggles faced by people on a personal level as they search for identity in a racially defined society. The moment of the protagonist’s engagement with her image in the mirror testifies to the effect of society on the self, pointing to the origin of prejudice and the desire to be accepted in a certain kind of society. The research explores how Hamid portrays the identity of his characters as being in constant flux and dependent on special and sociocultural circumstances. The findings imply that racism and identity are testing, clarifying the complicated relationships that influence experiences of people.